Synthesis and Characterization of -3D- Metal Complexes with 2-(Furan -2- Formyl Imino) Sulphanilamido Thiazole - NIRANJAN LAL; HIMANSHU; SHARMA; MUKTI VERMA (International Journal of Pharma and Bio Sciences, 2010)
The metal complexes of Mn (II), Ni (II), Co (II), Cu (II, and Zn (II) with 2-furan -2-formyl imino sulphanilamido thiazole are synthesized and characterized. The structure of the newly synthesized complexes and the ligands were established by using U.V., I.R., Magnetic moment study and elemental analysis.The ligand and the complexes were also screened for their fungicidal activity against different fungi Viz. Phoma-exigua. Macrophomina-phaseoli and Collechtotrichum – capsici.